Hydrogen process metallurgy: From ways of managing iron-bearing waste to hydrogen technology for steel smelting - Mróz, Jan; Szemalikowska, Alicja; Niesler, Marian; Stecko, Janusz (Ironmaking & steelmaking, 2025)
The article presents some aspects of the current trends in changes in the state of steel smelting technology in the world, which are an attempt to respond to the serious destabilization of climatic and environmental conditions in the world as a result of excessive global emissions of carbon dioxide, including by the iron and steel industry. Since the concept of sustainable development refers to the entire closed cycle of iron and steel production along with development prospects, the article consists of three chapters: I. Problems and methods of managing iron-bearing waste in iron and steel industry. II. Transformation of the traditional blast furnace – basic oxygen furnace steel smelting technology to low CO2 emission technologies. III. Net zero CO2 emissions (fossil-free) steelmaking technologies. Chapter I emphasizes that in the sustainable development of all technologies, the effective and environmentally harmless transformation of waste materials should be the priority throughout the entire steel technological and production chain. Chapter II refers to the necessary modernization projects in the current dominant two-stage technology for producing iron and steel: a blast furnace - a basic oxygen furnace. This technology is the main emitter of carbon dioxide in the iron and steel industry, including the production of blast coke. The gradual elimination of this method of steel production means that in the transitional period there will be a need to adapt existing blast furnace installations to the DRI process for producing metalized pellets. The problems of developing low-emission technologies for producing iron and steel are the subject of many projects conducted by many industry and university research centers. Chapter III mainly concerns the development of research on prospective zero-emission steel production technologies using hydrogen as an iron oxide reducer. The importance of this type of technological solutions for radically reducing CO2 emissions in the iron and steel industry seems to be decisive in the chain of modernization and transformation efforts, as well as research on new technologies in the iron and steel industry, which have been undertaken for many years.